Efficacy of Mometasone Furoate Nasal Spray with Oral Montelukast in the treatment of Otitis Media with Effusion with or without Adenoid Hypertrophy and Atopic diseases (Bangladesh Journal of Medical Science, 2022)
Bacground:Otitis media with effusion [OME] is a common chronic but silent disease of middle ear in children and is the commonest cause of hearing impairment, delayedlanguage development and altered quality of life.Though surgical management is the treatment of choice but now alternative medical treatment with steroid nasal spray is well accepted.Aim of this study: In this prospective, randomized placebo control study we want to observe the efficacy of Mometasone furoate nasal spray in conjunction with oral Leukotriene receptor blocker [Montelukast] in comparison to Mometasone furoate nasal spray only and normal saline spray as placebo for 3 months.Materials and Methods: Total sixty children aged 2-12 years old diagnosed with bilateral OME for at least 3 months with or without enlarged adenoid & atopic diseases, were randomly allocated into three equal groups. The first group A received Mometasonefouroate nasal spray plus Tab Montelukast for 12 weeks and second group B received only mometasonefouroate nasal spray &third group C received normal saline spray for the same duration.Result: Otoscopic clinical exam, Pure Tone audiometry & tympanometry were done at the end of treatment [3 months duration]. In otoscopic examination normal tympanic membrane finding show significant improvement in group A than group B & group C and tympanometric result in group A , show 80% improvement in middle ear status & had larger chi-square value then group B [60% improvement] and group C [10% improvement] and pure tone audiometry result show highest hearing threshold improved in group A and were more significant than group B and control group C.Conclusion: Mometasone furoate nasal spray is a much more effective medical treatment option in resulution of OME when it is combined with oral Leukotriene receptor blocker Montelukastas it helps to normalize the Eustachian tube function and middle ear status by decreasing enlarged adenoid size, atopic disorders and improving hearing power & quality of life.Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 836-841